Marginal adaptation of Spinell InCeram and feldspathic porcelain laminate veneers - Tahereh Ghaffari (Dental Research Journal, 2016)
Background: This in vitro study investigated the marginal fit of two porcelain laminate veneers to help the selection of more accurate veneers in discolored teeth. Materials and Methods: Thirty impressions of metal master die created from the prepared labial surface of an acrylic maxillary central incisor were made and poured with Type IV stone. The dies were distributed into test groups (n = 15) for the construction of DuCeram and InCeram laminate veneers. An image-analysis program was used to measure the gap between the veneers and the master die at the labial, lingual, and proximal margins. Statistical analysis was performed with repeated measures ANOVA. Independent t-test was used to compare the mean values between the two groups. Values of P < 0.05 were judged to be significant. Results: Differences between marginal fit of two groups were significant (P < 0.001). The overall mean marginal gap values (μm) for InCeram and DuCeram were, respectively, 114.4 ± 40.81 and 282.3 ± 82.82. Independent t-test revealed significant differences between the marginal gaps of two materials at different predetermined points. Conclusion: Within the limitations of this study, the marginal gap in InCeram laminate veneer was within the clinically acceptable standard set at 120 μm.